Linking Transformational and Transactional Leadership on Teacher Satisfaction during Digital Era - Asbari, Masduki (AGUSPATI RESEARCH INSTITUTA, 2024)
- This research aims to measure the influence of the principal's leadership style on teacher job satisfaction which is mediated by teacher job perceptions. Data collection was carried out through quantitative questionnaires with simple random sampling via electronics to the teacher population in Banten. The results of the questionnaire that were returned and valid were 865 samples. Data processing used the SEM method with SmartPLS 3.0 software. The results of this research conclude that transformational leadership has a positive and significant effect on teacher satisfaction, both directly and indirectly through the mediation of teachers' job perceptions. Meanwhile, transactional leadership does not have a significant effect on teacher satisfaction, either directly or indirectly through the mediation of teachers' work perceptions.